SPECTROPHOTOMETRIC METHOD FOR THE DETERMINATION OF BROMHEXINE HYDROCHLORIDE IN PURE AND PHARMACEUTICAL PREPARATIONS - Al-Ward, Hind (Iraqi Journal of Science, 2024)
A new simple and sensitive spectrophotometric method has been developed for the determination of Bromhexine Hydrochloride in pure form and pharmaceutical preparations. The method is based on the diazotization reaction of Bromhexine Hydrochloride with sodium nitrite in hydrochloric acid medium to form diazonium salt, which is coupled with chromotropic acid to form a red water-soluble azo dye, that has a maximum absorption at λmax = 507 nm. Beer’s law is obeyed over the concentration range (2-60 μg.ml-1) with RSD less than 2.050% and molar absorptivity of 1.569x104 l.mol-1.cm-1 and Sandell sensitivity of 0.0262 μg.cm-2. The method was applied successfully for the determination of Bromhexine Hydrochloride in pharmaceutical preparations.